A Near-Fatal Infection with Oseltamivir-Resistant Seasonal Influenza A in a Previously Healthy Child: Case Report - Jesse Papenburg; Christos Karatzios; Yan Li; Nathalie Bastien; Makeda Semret; Dorothy Moore (Canadian Journal of Infectious Diseases and Medical Microbiology)
A case of near-fatal oseltamivir-resistant seasonal influenza A infection in a previously healthy four-year-old boy is reported. This case highlights three important points for physicians: oseltamivir-resistant influenza A (H1N1) has recently emerged in North America; contrary to previously held beliefs, such strains are capable of causing severe disease in healthy children; and given this change in epidemiology, clinicians caring for children with severe seasonal influenza A infection should consider empiric dual therapy with oseltamivir and amantadine.